An Observational Analysis of a Novel Digital Rectoscope. Issue 12 (December 2021) - Lewis, James A.; Khan, Shabuddin; Tilney, Henry S.; Wilson, Jonathan M.; Vitone, Louis J.; Souvatzi, Maria; Singh, Baljit; Kinross, James M.
Abstract : BACKGROUND: This is an analysis of the first 50 in-human uses of a novel digital rigid sigmoidoscope. The technology provides digital image capture, telemedicine capabilities, improved ergonomics, and the ability to biopsy under pneumorectum while maintaining the low cost of conventional rigid sigmoidoscopy. The primary outcome was adverse events, and the secondary outcome was diagnostic view. PRELIMINARY RESULTS: Fifty patients underwent outpatient (n = 25) and surgical rectal assessment (n = 25), with a mean age of 60 years. This included 31 men and 19 women with 12 different clinical use indications. No adverse events were reported, and no defects were reported with the instrumentation. Satisfactory diagnoses were obtained in 48 (96%) of 50 uses, images were captured in 48 (96%) of 50 uses, and biopsies were successfully taken in 13 uses (26%). No adverse events were recorded. Independent reviewers of recorded videos agreed on the quality and diagnostic value of the images with a κ of 0.225 (95% CI, 0.144–0.305) when assessing whether the target pathology was adequately visualized. IMPACT OF INNOVATION: The improved views afforded by digital rectoscopy facilitated a satisfactory clinical diagnosis in 96% of uses. The device was successfully deployed in the operating room and outpatients irrespective of bowel preparation method, where it has the potential to replace flexible sigmoidoscopy for specific use cases. The technology provides a high-quality image and video that can be securely recorded for documentation and medicolegal purposes with agreement between blinded users despite a lack of standardized training and heterogenous pathology. We perceive significant impact of this technology for the assessment of colorectal anastomoses, the office management of colitis, "watch and wait, " and for diagnostic support in rectal cancer diagnosis. The technology has significant potential to facilitate proctoring and training, and it now requires prospective trials to validate its diagnostic accuracy against more costly flexible sigmoidoscopy systems.